Exploring coaching style preference through conversations about coaching and personality - Farheen Jeelani; Gregory Fantham; Marais Bester (Coaching Psykologi: The Danish Journal of Coaching Psychology, 2020)
This paper presents the results of a mixed method study exploring coachees’ perspectives on the impact and helpfulness of personality theory and assessments in applying different coaching styles. Participants included 20 individuals who had been coached in the past, of different nationalities and from various industries, who took part in both the qualitative and the quantitative studies. The following consistent themes emerged from the qualitative study: the importance of personality validity, the impact of the coaching relationship, the perceived effectiveness of coaching, reflecting on past experiences and moving forward toward the future, while the quantitative results showed that individuals with certain Big Five personality traits preferred certain coaching styles over others. The study provides preliminary insights for coaches seeking to apply personality theory and personality assessments in their coaching practices and may assist them to make informed decisions about the coaching style to adopt in order to improve coaching relationships and coaching effectiveness.